Stakeholder-based governance for managing victims of violence against women and children in East Java - Rodiyah, Isnaini; Irianto, Jusuf (Masyarakat, Kebudayaan dan Politik, 2024)
The number of domestic violence has increased. Meanwhile, until now it has not been possible to identify the stakeholder groups involved and need to be involved in providing solutions to prevent and manage victims of violence. A stakeholder-based governance system can be considered to manage victims of violence both preventively, curatively and rehabilitatively. The purpose of this study is to describe stakeholder-based governance to deal with victims of violence against women and children. This research was conducted at the East Java Integrated Service Center for the Protection of Women and Children (P2T-PPA) which has owned and implemented stakeholderbased governance. Data were collected through Focus Group Discussion (FGD) activities with qualitative data analysis methods. The FGDs involved representatives from each stakeholder in the management of victims of violence against women. The results showed that the stakeholder-based governance system is able to overcome various barriers to communication, coordination, and synergy in dealing with victims more quickly, accurately, and comprehensively. This study concludes that stakeholder-based governance for women and children is the best approach because it is able to integrate all related parties, especially if it is supported by early detection technology to treat victims' trauma conditions in a curative and rehabilitative manner.